Dietary black soldier fly larvae mealsupplementation improves growth performance of juvenile Megalobrama amblycephala by remodeling intestinal energy metabolism - Wenqiang Jiang; Yan Lin; Xiangping Kong; Siyue Lu; Zhengyan Gu; Xiaomei Ye; Honghua Huan; Linghong Miao (Aquaculture, 2026)

Temporal and spatial characteristics of deep convective clouds: CloudSat/CALIPSO observations analyzed - Yan Dong; Yan Wang; Yangyang Gu; Minxia Zhang; Ruozhu Yang; Keying Qian; Delin Xu; Naifeng Lin (Journal of Atmospheric and Solar-Terrestrial Physics, 2026)

Built-in electric field-driven d-band engineering in metal sulfide heterojunctions for high-efficiency electro-Fenton degradation of antibiotics - Xiangwei Zou; Yue Wang; Xinyu Wang; Lin Lin; Xiao-yan Li; Chitou Lei; Xiaojun Fan; Weng Ian Ieong; Qinfen Gu; Lianpeng Sun; Chao Yang (Chemical Engineering Journal, 2026)

Lactococcus cremoris subsp. sagaensis subsp. nov., Isolated from Naturally Fermented Yogurt - Lin Cheng; Tian-Xue Wang; Chun Yan Li; Chaoxin Man; Chun Tao Gu (Current Microbiology, 2026)

Single-nucleus RNA sequencing reveals cellular heterogeneity in Holstein dairy cows with different milk production volumes - Chuanchuan Wang; Yafei Chen; Xiaofang Feng; Chao Yan; Yun Ma; Xiaohua Tian; Xiaoyun Ji; Lin Xue; Hua Wang; Juan Zhang; Yaling Gu (Food Bioscience, 2026)

Steric hindrance modulation in covalent triazine frameworks enables ultrahigh SO2 and SF6 capture - Xiaoyu Wang; Zhaosheng Fan; Lin Hu; Chang Liu; Xiaocui Xie; Xiaojuan Gu; Mingxuan Liu; Yixian Du; Xu Yan; Chen Chen; Xiongli Liu; Lin Li; et al. (Chemical Engineering Journal, 2026)

Infection risks associated with b/tsDMARDs in rheumatoid arthritis: a systematic review and network meta-analysis - Xue-Mei Zhang; Li Liu; Yi-Dan Yan; Zai-Li Zhang; Ke-Jia Le; Yang-Xi Liu; Xiao-Jun Ni; Liang-Jing Lu; Guo-Hua Zhou; Zhi-Chun Gu; Jia Li; Hou-Wen Lin (European Journal of Clinical Pharmacology, 2026)

ERBB2 as a Prognostic Biomarker in Prostate Cancer: Integration of Single-Cell Transcriptomics, Deep Learning, and Immunohistochemical Validation - Chen Wang; Li-Jing Zhu; Wei-Bo Mao; Ting Chen; Teng-Fei Gu; Sheng-Ping Hu; Yong-Tao Pan; Guo-Lin Yan; Yun-Peng Dong; Jie Li (Biochemical Genetics, 2026)

Functional noncoding variants within the TBX1 enhancer contribute to tetralogy of Fallot - Jimiao Gao; Tao Jiang; Yingyi Quan; Xinyue Liu; Min Da; Jiang Jiang; Jun Zhou; Hao Sun; Yan Zhou; Wanting Ma; Zicheng Zhang; Yiwei Cheng; et al. (Science China Life Sciences, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Precise perception of surface tackiness enabled by a soft single-sensing-element tactile sensor - Ying Yang; Mingwei Gu; Jia-Sen Xie; Xingyu Ma; Yan-Na Lu; Lin Zheng; Jinhui Gu; Junshuai Chen; Yunjie Lu; Denys Makarov; Jin Ge (Science Bulletin, 2026)

A high-performance bimodal sub-nanoporous polyelectrolyte complex membrane for organic solvent nanofiltration constructed by MOF-reinforced nano-unit - Hui-Qian Huo; Bing-Xin Gu; Jin-Lin Wang; Jia-Chen Zhang; Kai Zhang; Ming-Jie Yin; Yan-Li Ji; Quan-Fu An (Chemical Engineering Journal, 2026)

Chlorine-resistant high-entropy spinel oxide catalyst for efficient and durable seawater anion exchange membrane water electrolysis - Thi Xuyen Nguyen; Ting-You Shih; Ngoc Thanh Thuy Tran; Thanh Tuan Nguyen; Yi-Chuan Chu; Bo-Han Lai; Chun-Kuo Peng; Yu-Ru Lin; Yan-Gu Lin; Kao-Shu Chuang; Jeng-Kuei Chang; Thi Y Phung Nguyen; et al. (Chemical Engineering Journal, 2026)

Vesicles for cell crosstalk in bone: composition, function and application - Chenhui Gu; Yiyu Chen; Pengyu Chen; Hongsen Tian; Junchen Jiang; Zijie Wang; Huige Yan; Xianfeng Lin (Science China Life Sciences, 2026)

An advanced multifunctional strategy - enabled triboelectric nanogenerator for efficient wind-energy harvesting - Bin Wang; Yan Gu; Yan Zhou; Yamei Liu; Ning Huang; Guangze Du; Xinyang Liu; Lingling Han; Huibo Zhao; Zhen Wang; Yingao Xue; Jieqiong Lin (Chemical Engineering Journal, 2026)

Influence of calcination temperature on nutrient removal from aquaculture wastewater by composite substrate made of pyrite and biochar - Bolin Huang; Gang Peng; Yan Zhang; Lin Tan; Shiyang Zhang; Siyuan Wu; Qirui Zhang; Long He; Zhaojun Gu; Xingguo Liu (Journal of Environmental Chemical Engineering, 2026)

Magic chain-flip triboelectric nanogenerator for multi-mode wind and raindrop energy harvesting - Mingxia Chen; Jiahong Yang; Rui Gu; Hai Yan; Zhenghao Li; Siqi Sun; Nuo Xu; Ziwei Huo; Zhong Lin Wang; Qijun Sun; Xiangde Lin (Chemical Engineering Journal, 2026)

Structural characteristics and bioactivities of an exopolysaccharide from mycelial fermentation of a medicinal fungus Cs-HK1 - Fang Ting Gu; Jun Hui Li; Zi Chen Zhao; Yan Yu Zhu; Lin Xi Huang; Jian Yong Wu (Carbohydrate Polymers, 2026)

Unveiling the simultaneous organophosphate esters degradation mechanisms in biological wastewater nitrogen removal systems under varying phosphorus source conditions: Microbial insights and ecological interactions - Ziyuan Lin; Ziyu Yan; Weihao Kong; Yingwei Zhou; Yili Xu; Jiayi Xie; Weikang Gu; Benzhou Gong; Yancheng Li; Chaolan Zhang (Journal of Hazardous Materials, 2026)

Editorial Expression of Concern: Minocycline Protects Against NLRP3 Inflammasome-Induced Inflammation and P53-Associated Apoptosis in Early Brain Injury After Subarachnoid Hemorrhage - Jianru Li; Jingsen Chen; Hangbo Mo; Jingyin Chen; Cong Qian; Feng Yan; Chi Gu; Qiang Hu; Lin Wang; Gao Chen (Molecular Neurobiology, 2026)

Precise measurements of the cosmic ray proton energy spectrum in the “knee” region - Zhen Cao; F. Aharonian; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; C.M. Cai; W.Y. Cao; Zhe Cao; et al. (Science Bulletin, 2025)

Biomass electrooxidation-involved carbon radicals boost electrochemiluminescence - Qie Fang; Lin Xu; Lijin Wang; Jingshuai Li; Yan Zhou; Yifei Chen; Wenxuan Jiang; Liuyong Hu; Wenling Gu; Chengzhou Zhu (Science Bulletin, 2025)

Clastic record from Northern Tethyan Himalaya: Implication for the initial India-Asian collision in the western Yarlung-Zangpo suture zone, South Tibet - Xu-dong Guo; Lin Ding; Fu-long Cai; Gui-zhen Guo; Xiao-yan Xu; Peng Han; Chang-jun Gu; Mei-yu Liu; Xiang-li Ding; Xu Liu; Xin-lei Li; Deng Zeng; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Molecular dynamics simulation-driven focused virtual screening and experimental validation of Fisetin as an inhibitor of Helicobacter pylori HtrA protease - Li Gao; Xianqiong Jiang; Hongtao Duan; Yan Shen; Kui Gu; Kuilong Huang; Yuanqiang Wang; Mao Shu; Rui Zhang; Zhihua Lin (Molecular Diversity, 2025)

Effect of calcium chelation on the physio-chemical characteristics and rehydration behavior of spray-dried casein-rich powder - Qiantong Zhong; Shucan Luo; John Fizpatrick; Langye Jiang; Zonglin Guo; Jie Lin; Hua Zheng; Haili Zeng; Canhu Wu; Songbai Zheng; Yan Gu; Christelle Turchiuli; et al. (Journal of Food Engineering, 2025)

Experimental study, finite element simulation and theoretical analysis on punching shear capacity of steel-ECC composite slabs - Youzhu Lin; Di Yao; Ge Gao; Tianfei Gu; Ming Sun; Jiachuan Yan (Engineering Structures, 2025)

How to promote green transformation of mariculture industry under the influence of financial constraints? A policy simulation based on peer incentive perspective - An Yan; Ying Liu; Chunyu Lin; Wenwen Gu; Qiaorong Yin; Xiumei Fu (Marine Pollution Bulletin, 2025)

A copper-based single-atom material effectively controls plant diseases with nearly zero soil residue and low phytotoxicity - Rui Huang; Yong Yan; Yafei Jiang; Chunyan Gu; Zhentao Ma; Lifang Xue; Yao Ma; Xingen Lin; Juan Zhang; Ran Shi; Yiwen Wang; Linjing Liu; et al. (Science Bulletin, 2025)

Corrigendum to “Engineered zwitterionic hydrogel with extreme environment resilience: High ionic conductivity, subzero tolerance, and potential for multimodal sensing and optical applications across devices” [Chem. Eng. J. 510 (2025) 161390/CEJ 161390] - Yan-Na Lu; Kai Mo; Mingwei Gu; Jia-Sen Xie; Ying Yang; Lin Zheng; Xiang-Ru Liu; Yunjie Lu; Jun-Shuai Chen; Jin Ge (Chemical Engineering Journal, 2025)

Robust LiF/LiCl-rich SEI layer via composite electrolyte design enables long-cycling all-solid-state lithium metal batteries - Chengdeng Wang; Jun Wu; Jiamao Hao; Lin Zhong; Lu Yang; Jiashuai Wang; Zhi Wang; Xiangrui Chen; Liyuan Bai; Jinpeng Li; Yan Gao; Xiaoqin Yan; et al. (Chemical Engineering Journal, 2025)

Antimicrobial properties and preservation potential of Allium sativum L-derived extracellular vesicle-like particles for food applications - Chenqi Zhu; Xiaoxiao Ke; Yi Gu; Chunmeng Wang; Shangyang Lin; Yijie Qian; Jiale Cheng; Yan Chen; Liu Xu; Zhipeng Chen (Food Chemistry, 2025)

Tailoring Cu3Nx clusters on TiO2 nanosheets to the sub-nanometric scale for enhancing NH3 photosynthesis - Hyun Sik Moon; Yu-Jeong Yang; Getasew Mulualem Zewdie; Geon Youn; Yi-An Chen; Yu-Peng Chang; Kai-Chi Hsiao; Ting-Han Lin; Yi-Dong Lin; Jun Kue Park; Jucheol Park; Yan-Gu Lin; et al. (Chemical Engineering Journal, 2025)

Epigenetics in the modern era of crop improvements - Yan Xue; Xiaofeng Cao; Xiangsong Chen; Xian Deng; Xing Wang Deng; Yong Ding; Aiwu Dong; Cheng-Guo Duan; Xiaofeng Fang; Lei Gong; Zhizhong Gong; Xiaofeng Gu; et al. (Science China Life Sciences, 2025)
Epigenetic mechanisms are integral to plant growth, development, and adaptation to environmental stimuli. Over the past two decades, our comprehension of these complex regulatory processes has expanded remarkably, producing a substantial body of knowledge on both locus-specific mechanisms and genome-wide regulatory patterns. Studies initially grounded in the model plant Arabidopsis have been broadened to encompass a diverse array of crop species, revealing the multifaceted roles of epigenetics in physiological and agronomic traits. With recent technological advancements, epigenetic regulations at the single-cell level and at the large-scale population level are emerging as new focuses. This review offers an in-depth synthesis of the diverse epigenetic regulations, detailing the catalytic machinery and regulatory functions. It delves into the intricate interplay among various epigenetic elements and their collective influence on the modulation of crop traits. Furthermore, it examines recent breakthroughs in technologies for epigenetic modifications and their integration into strategies for crop improvement. The review underscores the transformative potential of epigenetic strategies in bolstering crop performance, advocating for the development of efficient tools to fully exploit the agricultural benefits of epigenetic insights.

Potential links between the progress in environmental governance and the prevalence of mental disorder burden: New insight from a dynamic panel-data analysis for 197 countries - Jun-Yan Xi; Li-Chang Chen; Xue-Qi Li; Jie Hu; Wei Hu; Jian-Jun Bai; Yi-Ning Xiang; Yu-Can Zhang; Jia-Jia Wang; Shi-Hao Wang; Jing Gu; Yuan-Tao Hao; et al. (Sustainable Cities and Society, 2025)

Exposure to polyethylene terephthalate micro(nano)plastics exacerbates inflammation and fibrosis after myocardial infarction by reprogramming the gut and lung microbiota and metabolome - Xin Gu; Zhixuan Zhang; Lin Zhao; Lijie Lu; Xin Lu; Yafei Li; Tianya Gu; Xin Huang; Guangyi Huang; Yan Liang; Haoyu Meng; Baihong Li; et al. (Journal of Hazardous Materials, 2025)

Synergistic modulation of electronic structure in high entropy perovskite oxide for enhanced bifuntional oxygen evolution/reduction reactions and its mechanistic insights via in-situ analyses and density functional theory calculation - Thi Xuyen Nguyen; Chih-Heng Lee; Jun-Hong Sun; Chun-Kuo Peng; Wen-Hui Chu; Hamed Pourzolfaghar; Yu-Ru Lin; Muhammad Ghufron; Yuan-Yao Li; Yu-Hao Chang; Yan-Gu Lin; Hsin-Yi Tiffany Chen; et al. (Chemical Engineering Journal, 2025)

Engineered zwitterionic hydrogel with extreme environment resilience: High ionic conductivity, subzero tolerance, and potential for multimodal sensing and optical applications across devices - Yan-Na Lu; Kai Mo; Mingwei Gu; Jia-Sen Xie; Ying Yang; Lin Zheng; Xiang-Ru Liu; Yunjie Lu; Jun-Shuai Chen; Jin Ge (Chemical Engineering Journal, 2025)

Dietary retinoic acid improved the growth, lipid metabolism and immune status in Macrobrachium rosenbergii - Qin-Cheng Huang; Li Wang; Zhi-Min Gu; Cui Liu; Tian-Tian Ye; Jun-Jun Yan; Ji-Lun Meng; Yu-Tong Zheng; Xian-Ping Ge; Zhi-Deng Lin; Guo-Yuan Zou (Frontiers in Marine Science, 2025)
The effect of dietary retinoic acid (RA) on the growth, lipid deposition, oxidation resistance, immunity, hepatopancreatic and intestinal health of Macrobrachium rosenbergii was evaluated. A total of 1200 prawns (0.22 ± 0.00 g) were divided into six groups and fed their corresponding feed containing 4, 132, 296, 562, 1206 or 2562 mg/kg dietary RA. The weight gain rate, specific growth rate and final body weight of the prawns changed linearly and quadratically, with the maximum observed in those fed 296 mg/kg dietary RA. Increasing dietary RA linearly and quadratically raised the RA content in the whole body. Compared to the prawns fed 4 mg/kg dietary RA, there was significantly lower lipid deposition in the muscle, hepatopancreas and whole body of prawns fed 296 mg/kg dietary RA. Prawns fed 296 mg/kg dietary RA had lower triglyceride (TG) content in the hepatopancreas with upregulated gene expression of retinoid X receptor ( RXR ), diacylglycerol acyltransferase 1 ( dgat1 ) and carnitine palmitoyltransferase 1 ( cpt1 ). Additionally, 296 mg/kg dietary RA increased the protein expression of RXR, CAMKKβ and phospho-AMPK. A dietary RA level of 296 mg/kg could decrease oxidative stress by upregulating the expression of peroxiredoxin 5 ( prx5 ) and improve immunity by upregulating expression of toll - like receptor 2 ( toll2 ), myeloid differentiation factor 88 (myd88 ) and dosal in the hepatopancreas. The intestinal health related genes ( crustin 2 / 3 / 4 , anti-lipopolysaccharide factor 1 / 7 , prx5 , peritrophin-1 , myosin light chain kinase , claudin , myd88 and dosal ) and morphological structure were also positively affected by dietary RA. Furthermore, dietary RA could relieve the immune responses induced by lipopolysaccharide, thus leading to lower transcription of antimicrobial peptides. In summary, dietary RA could improve the growth, lipid utilisation, antioxidant capacity and immunity of M . rosenbergii . To avoid the negative effects of excessive addition and obtain optimal growth, a diet containing 296 mg/kg dietary RA was suggested by the present study.

Acidosis induces autophagic cell death through ASIC1-mediated Akt/mTOR signaling in HT22 neurons - Miao Guo; Ming-Yue Qiu; Lin Zeng; Ya-Xiong Nie; Ya-Ling Tang; Yan Luo; Hong-Feng Gu (Toxicology, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Metabolic outcomes of Cordyceps fungus and Goji plant polysaccharides during in vitro human fecal fermentation - Fang Ting Gu; Jun Hui Li; Zi Chen Zhao; Yan Yu Zhu; Lin Xi Huang; Jian Yong Wu (Carbohydrate Polymers, 2025)

Nicotinamide riboside restores nicotinamide adenine dinucleotide levels and alleviates brain injury by inhibiting oxidative stress and neuroinflammation in a mouse model of intracerebral hemorrhage - Jing She; Hua Zhang; Hui Xu; Yan-Yan Li; Jun-Chao Wu; Rong Han; Fang Lin; Yan Wang; Rui Sheng; Jin-hua Gu; Zheng-Hong Qin (Molecular Neurobiology, 2025)
Hemorrhagic stroke is a global health problem owing to its high morbidity and mortality rates. Nicotinamide riboside is an important precursor of nicotinamide adenine dinucleotide characterized by a high bioavailability, safety profile, and robust effects on many cellular signaling processes. This study aimed to investigate the protective effects of nicotinamide riboside against collagenase-induced hemorrhagic stroke and its underlying mechanisms of action. An intracerebral hemorrhage model was constructed by stereotactically injecting collagenase into the right striatum of adult male Institute for Cancer Research mice. After 30 minutes, nicotinamide riboside was administered via the tail vein. The mice were sacrificed at different time points for assessments. Nicotinamide riboside reduced collagenase-induced hemorrhagic area, significantly reduced cerebral water content and histopathological damage, promoted neurological function recovery, and suppressed reactive oxygen species production and neuroinflammation. Nicotinamide riboside exerts neuroprotective effects against collagenase-induced intracerebral hemorrhage by inhibiting neuroinflammation and oxidative stress.

Soil microbial diversity in boreal forests of China: A case study of the Altai Mountains with an emphasis on core microbiomes - Gu Rao; Wen-Long Song; Di Lin; Ya-Jing Chen; Shu-Zhen Yan; Shuang-Lin Chen (Applied Soil Ecology, 2025)

Priority sources identification and risks assessment of heavy metal(loid)s in agricultural soils of a typical antimony mining watershed - Lianhua Liu; You Li; Xiang Gu; Roberto Xavier Supe Tulcan; Lingling Yan; Chunye Lin; Junting Pan (Journal of Environmental Sciences, 2025)

Outstanding comprehensive energy storage performance in BNT-based lead-free ceramics via synergistic optimization strategy - Zixin Li; Wenjie Zhou; Jinming Guo; Xinye Lv; Shuxin Lin; Yilang Li; Long Gu; Fei Yan (Chemical Engineering Journal, 2025)

Three-dimensional Heterogeneity and Intrinsic Plasticity of the Projection from the Cerebellar Interposed Nucleus to the Ventral Tegmental Area - Chen Wang; Si-Yu Wang; Kuang-Yi Ma; Zhao-Xiang Wang; Fang-Xiao Xu; Zhi-Ying Wu; Yan Gu; Wei Chen; Ying Shen; Li-Da Su; Lin Zhou (Neuroscience Bulletin, 2025)

Cohort Studies and Multi-omics Approaches to Low-Dose Ionizing Radiation-Induced Cardiovascular Disease: A Comprehensive Review - Xumin Zong; Lin Zhu; Yan Wang; Jinhan Wang; Yeqing Gu; Qiang Liu (Cardiovascular Toxicology, 2025)

Endoplasmic reticulum stress and Ca2+ dysregulation in response to ammonia nitrogen exposure could be alleviated by dietary fermented mulberry leaf meal in Megalobrama amblycephala - Wenqiang Jiang; Linjie Qian; Qiaoqiao Mu; Yan Lin; Siyue Lu; Zhengyan Gu; Huaishun Shen; Xianping Ge; Linghong Miao (Aquaculture, 2024)

A novel collaborative collision avoidance decision method for multi-ship encounters in complex waterways - Han Dong; Rong Zhen; Qiyong Gu; Zhong Lin; Jiuhu Chen; Kai Yan; Bing Chen (Ocean Engineering, 2024)

Bifidogenic properties of polysaccharides isolated from mushroom Lentinula edodes and enhanced immunostimulatory activities through Bifidobacterial fermentation - Lin Xi Huang; Fang Ting Gu; Yan Yu Zhu; Zi Chen Zhao; Jun Hui Li; Jian Yong Wu (Food Bioscience, 2024)

Pyrene-encapsulated light-emitting π-conjugated polymer with excellent ozone tolerance capacity for large-area and flexible ultra-deep-blue PLEDs with CIEy = 0.08 - Hao Li; Mengna Yu; Yang Li; Manman Luo; Jingyao Ma; Yahui Zhang; Yeyang Wang; Yunlong Zhang; Yan Ma; Lubing Bai; Qiujing Bao; Jiabin Gu; et al. (Chemical Engineering Journal, 2024)

Simulated human digestion and fermentation of a high-molecular weight polysaccharide from Lentinula edodes mushroom and protective effects on intestinal barrier - Jun Hui Li; Fang Ting Gu; Ye Yang; Zi Chen Zhao; Lin Xi Huang; Yan Yu Zhu; Shiguo Chen; Jian Yong Wu (Carbohydrate Polymers, 2024)

Loss of CHCHD2 Stability Coordinates with C1QBP/CHCHD2/CHCHD10 Complex Impairment to Mediate PD-Linked Mitochondrial Dysfunction - Yan-Lin Ren; Zheng Jiang; Jia-Yi Wang; Qin He; Si-Xu Li; Xiao-Jing Gu; Yang-Ran Qi; Min Zhang; Wen-Jie Yang; Bei Cao; Jing-Yu Li; Yi Wang; et al. (Molecular Neurobiology, 2024)

Evidence for particle acceleration approaching PeV energies in the W51 complex - Zhen Cao; F. Aharonian; Axikegu; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; Q. Cao; W.Y. Cao; et al. (Science Bulletin, 2024)

A novel physics-based cloud retrieval algorithm based on neural networks (CRANN) from hyperspectral measurements in the O2-O2 band - Wenwu Wang; Husi Letu; Huazhe Shang; Jian Xu; Huanhuan Yan; Lianru Gao; Chao Yu; Jianbin Gu; Jinhua Tao; Na Xu; Lin Chen; Liangfu Chen (Remote Sensing of Environment, 2024)

Discovery and Exploration of Lipid-Modifying Drug Targets for ALS by Mendelian Randomization - Zheng Jiang; Xiao-Jing Gu; Wei-Ming Su; Qing-Qing Duan; Kang-Fu Yin; Yan-Lin Ren; Yi Wang; Bei Cao; Yong-Ping Chen (Molecular Neurobiology, 2024)

Insight into mitigation mechanisms of N2O emission by biochar during agricultural waste composting - Jun Liu; Yunlong Hu; Sijia Gu; Xuemei Li; Zhanglong Ji; Hao Qin; Lihua Zhang; Jiachao Zhang; Hongli Huang; Binghua Yan; Lin Luo (Bioresource Technology, 2024)

Metabolomics signature of blood pressure salt sensitivity and its link to cardiovascular disease: A dietary salt-intervention trial - Zhennan Lin; Jianxin Li; Fangchao Liu; Jie Cao; Shufeng Chen; Jichun Chen; Keyong Huang; Yaqin Wang; Hongfan Li; Yan Wang; Jianfeng Huang; Dongfeng Gu; et al. (Science China Life Sciences, 2024)

Stabilizing high-Ni cathodes with gradient surface Ti-enrichment - Wenchang Zhu; Xiaotian Zhu; Jizhen Qi; Junyi Yao; Yanbin Shen; Guanjian Cheng; Xue Huang; Shiqi Yang; Hao Zhang; Chao-Lung Chiang; Yan-Gu Lin; Jianming Bai; et al. (Chemical Engineering Journal, 2024)

'Environmental standard limit concentration' arsenic exposure is associated with anxiety, depression, and autism-like changes in early-life stage zebrafish - Yuanhui Zhu; Qianlei Yang; Jie Gu; Zhicheng Chen; Nan Jing; Tingxu Jin; Jiayuan Lin; Xin Wang; Jingwen Hu; Guixiang Ji; Yan An (Journal of Hazardous Materials, 2024)

Multi-functional hydrogen- and oxygen-capturing FeCo-N-C catalyst with improved hydrogenation of nitroarenes and ORR activity - Hsiu-Chung Tu; Yu-Lin Hsiao; Yi-Dong Lin; Yan-Gu Lin; Ding-Liang Liao; Ko-Shan Ho (Chemical Engineering Journal, 2024)

Identification of the domestication gene GmCYP82C4 underlying the major quantitative trait locus for the seed weight in soybean - Yang Li; Wenqian Zhao; Jiajun Tang; Xiuli Yue; Jinbao Gu; Biyao Zhao; Cong Li; Yanhang Chen; Jianbo Yuan; Yan Lin; Yan Li; Fanjiang Kong; et al. (Theoretical and Applied Genetics, 2024)

An intrusion and environmental effects of man-made silver nanoparticles in cold seeps - Kelei Zhu; Jiawei Liu; Mingyu Zhao; Lulu Fu; Zengfeng Du; Fanqi Meng; Lin Gu; Peiyu Liu; Yan Liu; Chaoqun Zhang; Xin Zhang; Jinhua Li (Science of The Total Environment, 2024)

Mechanism of sulfur-guided CO2 selective hydrogenation through modulation of surface intermediate over Ni/ZrO2 catalysts - Yunhao Zang; Ziyi Zhang; Yan Wang; Jiangying Qu; Feng Gao; Jianfeng Gu; Xuetan Lin; Taipeng Wei (Chemical Engineering Journal, 2024)

Highly effective degradation of ibuprofen by alkaline metal-doped copper oxides via peroxymonosulfate activation: Mechanisms, degradation pathway and toxicity assessments - Meng-Wei Zheng; Cheng-Wei Lin; Pei-Hsin Chou; Chao-Lung Chiang; Yan-Gu Lin; Shou-Heng Liu (Journal of Hazardous Materials, 2024)

Climate-shaped vegetation dominated the spatial pattern of the Bowen ratio over terrestrial ecosystems in China - Mingyu Sun; Guirui Yu; Zhi Chen; Tianxiang Hao; Meng Yang; Xianjin Zhu; Weikang Zhang; Lang Han; Zhaogang Liu; Lexin Ma; Xiaojun Dou; Yuan Yao; et al. (Agricultural and Forest Meteorology, 2024)

Ecosystem responses dominate the trends of annual gross primary productivity over terrestrial ecosystems of China during 2000–2020 - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Hua Qi; Meng Yang; Zhao-Gang Liu; Xiao-Jun Dou; Le-Xin Ma; Shi-Ping Chen; et al. (Agricultural and Forest Meteorology, 2023)

Distribution, assembly, and interactions of soil microorganisms in the bright coniferous forest area of China's cold temperate zone - Gu Rao; Shu-Zhen Yan; Wen-Long Song; Di Lin; Ya-Jing Chen; Shuang-Lin Chen (Science of The Total Environment, 2023)

Assessing the causal relationship between immune traits and systemic lupus erythematosus by bi-directional Mendelian randomization analysis - Jie Gu; Guan-Min Yan; Xiao-Lin Kong; Yin-Ying Zhang; Li-Hong Huang; Hui-Min Lu (Molecular Genetics and Genomics, 2023)

Targeted isolation of ursane-type triterpenoids from Tragopogon porrifolius based on Feature-Based Molecular Networking - Hong-bing Sun; Hai-fei Zou; Bing Xia; Yu-cheng Gu; Wen-lin Wu; Yan Zhou (Phytochemistry Letters, 2023)

Moringa oleifera Lam. leaves as new raw food material: A review of its nutritional composition, functional properties, and comprehensive application - Min Yang; Liang Tao; Xin-Rui Kang; Zi-Lin Wang; Ling-Yan Su; Ling-Fei Li; Fan Gu; Cun-Chao Zhao; Jun Sheng; Yang Tian (Trends in Food Science & Technology, 2023)

The underappreciated importance of solar radiation in constraining spring phenology of temperate ecosystems in the Northern and Eastern United States - Yating Gu; Yingyi Zhao; Zhengfei Guo; Lin Meng; Kun Zhang; Jing Wang; Calvin K.F. Lee; Jing Xie; Yantian Wang; Zhengbing Yan; He Zhang; Jin Wu (Remote Sensing of Environment, 2023)

HtrA is involved in stress response and adhesion in Glaesserella parasuis serovar 5 strain Nagasaki - Xuan Zhang; Yan Lin; Xiaojuan Xu; Siting Wen; Zhichao Wang; Jiayun Gu; Qigai He; Xuwang Cai (Veterinary Microbiology, 2023)

Sulfur-induced electronic optimization of Mo5N6 for hydrogen evolution through topochemical substitution - Jianmei Chen; Xiaochun Liu; Hao Wang; Chao-Lung Chiang; Pengfei Hou; Jianmin Li; Huanyu Jin; Shujuan Liu; Xing Meng; Yan-Gu Lin; Jong-Min Lee; Qiang Zhao (Chemical Engineering Journal, 2023)

A green and designable natural deep eutectic solvent-based supramolecular solvents system: Efficient extraction and enrichment for phytochemicals - Zi-Hui Cai; Jian-Dong Wang; Lin Liu; Liu-Ding Ruan; Qi Gu; Xin-Yu Yan; Li-Na Fu; Peng-Quan Zhao; Su Zhang; Yu-Jie Fu (Chemical Engineering Journal, 2023)

Impacts of iron amendments and per-fluoroalkyl substances’ bio-availability to the soil microbiome in wheat ecosystem - Jian-yi Wu; Zu-lin Hua; Zhong-yan Liang; Li Gu (Chemosphere, 2023)

Mapping Chinese annual gross primary productivity with eddy covariance measurements and machine learning - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Shi-Ping Chen; Shao-Min Liu; Hui-Min Wang; Jun-Hua Yan; Jun-Lei Tan; Fa-Wei Zhang; et al. (Science of The Total Environment, 2023)

O-bridged Fe-W dual-atom co-anchored on carbon nitride for highly efficient solar-induced peroxymonosulfate activation - Yan Gu; Zhenhua Zhou; Zekai Lin; Xiaoli Liu; Tiefeng Xu; Wenxing Chen; Wangyang Lu (Chemical Engineering Journal, 2023)

Realizing the bifunctional electrocatalysis via local charge rearrangement of α-CrOOH-modulated Co@CoMoOx for overall water splitting - Suh-Ciuan Lim; Chao-Lung Chiang; Chun-Kuo Peng; Wen-Bin Wu; Yu-Chang Lin; Yu-Ru Lin; Chi-Liang Chen; Yan-Gu Lin (Chemical Engineering Journal, 2023)

Astragalus Polysaccharides Reduce High-glucose-induced Rat Aortic Endothelial Cell Senescence and Inflammasome Activation by Modulating the Mitochondrial Na+/Ca2+ Exchanger - Xin-Yu Miao; Xiao-Xiao Zhu; Zhao-Yan Gu; Bo Fu; Shao-Yuan Cui; Yuan Zu; Ling-Jun Rong; Fan Hu; Xiang-Mei Chen; Yan-Ping Gong; Chun-Lin Li (Cell Biochemistry and Biophysics, 2022)

Composition, Demographic History, and Population Structures of Trichiurus - Kui-Ching Hsu; Mu-Rong Yi; Sui Gu; Xiong-Bo He; Zhi-Sen Luo; Bin Kang; Hung-Du Lin; Yun-Rong Yan (Frontiers in Marine Science, 2022)
Sequences of the complete mitochondrial cytochrome oxidase subunit I gene were used to identify Trichiurus species and examine their population genetic structure and demographic history along the coast of China. Three Trichiurus species were found. Trichiurus japonicus lives in colder waters along the continental shelves in the China Seas, while Trichiurus nanhaiensis lives warmer waters along continental slopes in the South China Sea, and Trichiurus brevis lives in shallow and warmer waters in the South China Sea. The migrations of these species were mainly associated with feeding and spawning preferences. Two major wintering and spawning grounds in the East China Sea and South China Sea were found. All species showed a lack of population genetic structure resulting from their oceanodromous life cycle (the degree of population substructure index N ST = 0.000–0.149), but the results of approximate Bayesian computational approaches suggested population declines or stabilization and differentiation. The results of the T MRCA (time to the most recent common ancestor) showed that during glaciations, the Yellow Sea and the East China Sea were completely exposed, and the South China Sea acted as a refugium. Thus, the populations of these three species experienced differentiation during glaciations. This study also examined the limitations of Bayesian skyline plot analysis.

Mesenchymal stem cell-derived exosomes block malignant behaviors of hepatocellular carcinoma stem cells through a lncRNA C5orf66-AS1/microRNA-127-3p/DUSP1/ERK axis - Hao Gu; Chao Yan; Haijun Wan; Lin Wu; Junjie Liu; Zhiqiang Zhu; Dazhi Gao (Human Cell, 2021)

Differential DNA Methylation Profiles in Patients with Temporal Lobe Epilepsy and Hippocampal Sclerosis ILAE Type I - Wang Zhang; Haiyang Wang; Binchao Liu; Miaomiao Jiang; Yifei Gu; Shi Yan; Xian Han; Alicia Y. Hou; Chongyang Tang; Zhenfeng Jiang; Hong Shen; Meng Na; et al. (Journal of Molecular Neuroscience, 2021)

Wogonin Accelerates Hematoma Clearance and Improves Neurological Outcome via the PPAR-γ Pathway After Intracerebral Hemorrhage - Jianfeng Zhuang; Yucong Peng; Chi Gu; Huihui Chen; Zheng Lin; Hang Zhou; Xiao Wu; Jianru Li; Xiaobo Yu; Yang Cao; Hanhai Zeng; Xiongjie Fu; et al. (Translational Stroke Research, 2021)

Genipin Attenuates Tau Phosphorylation and Aβ Levels in Cellular Models of Alzheimer’s Disease - Meiting Li; Nan Cai; Liang Gu; Lijun Yao; Decheng Bi; Weishan Fang; Zhijian Lin; Yan Wu; Hong Xu; Hui Li; Zhangli Hu; Xu Xu (Molecular Neurobiology, 2021)

Association between population density and infection rate suggests the importance of social distancing and travel restriction in reducing the COVID-19 pandemic - Heliang Yin; Tong Sun; Lan Yao; Yan Jiao; Li Ma; Lin Lin; J Carolyn Graff; Lotfi Aleya; Arnold Postlethwaite; Weikuan Gu; Hong Chen (Environmental Science and Pollution Research, 2021)

Increased depression risk for elderly women with high blood levels of strontium and barium - Jia Lv; Yan-ling Li; Wen-qiang Ren; Rong Li; Jian-rong Chen; Chao Bao; Zhi-ping Du; Shun Feng; Ling Gu; Hui Gao; Kai-yong Liu; Lin-sheng Yang; et al. (Environmental Chemistry Letters, 2021)

Genotyping-by-sequencing to determine the genetic structure of a Tibetan medicinal plant Swertia mussotii Franch. - Yan Qiao; Fengxian Guo; Naxin Huo; Lin Zhan; Jiaqing Sun; Xixi Zuo; Zeguang Guo; Yong Q. Gu; Yi Wang; Yue Liu (Genetic Resources and Crop Evolution, 2021)

The substrate‐dependent regulatory effects of the AfeI /R system in Acidithiobacillus ferrooxidans reveals the novel regulation strategy of quorum sensing in acidophiles - Xue‐Yan Gao; Chang‐Ai Fu; Likai Hao; Xiu‐Feng Gu; Rui Wang; Jian‐Qiang Lin; Xiang‐Mei Liu; Xin Pang; Cheng‐Jia Zhang; Jian‐Qun Lin; Lin‐Xu Chen (Environmental Microbiology, 2021)
Summary A LuxI/R‐like quorum sensing (QS) system (AfeI/R) has been reported in the acidophilic and chemoautotrophic Acidithiobacillus spp. However, the function of AfeI/R remains unclear because of the difficulties in the genetic manipulation of these bacteria. Here, we constructed different afeI mutants of the sulfur‐ and iron‐oxidizer A . ferrooxidans , identified the N‐acyl homoserine lactones (acyl‐HSLs) synthesized by AfeI, and determined the regulatory effects of AfeI/R on genes expression, extracellular polymeric substance synthesis, energy metabolism, cell growth and population density of A . ferrooxidans in different energy substrates. Acyl‐HSLs‐mediated distinct regulation strategies were employed to influence bacterial metabolism and cell growth of A . ferrooxidans cultivated in either sulfur or ferrous iron. Based on these findings, an energy‐substrate‐dependent regulation mode of AfeI/R in A . ferrooxidans was illuminated that AfeI/R could produce different types of acyl‐HSLs and employ specific acyl‐HSLs to regulate specific genes in response to different energy substrates. The discovery of the AfeI/R‐mediated substrate‐dependent regulatory mode expands our knowledge on the function of QS system in the chemoautotrophic sulfur‐ and ferrous iron‐oxidizing bacteria, and provides new insights in understanding energy metabolism modulation, population control, bacteria‐driven bioleaching process, and the coevolution between the acidophiles and their acidic habitats.

Interferon-α2b spray inhalation did not shorten virus shedding time of SARS-CoV-2 in hospitalized patients: a preliminary matched case-control study - Shao-rui Hao; Ren Yan; Shan-yan Zhang; Jiang-shan Lian; Huan Cai; Xiao-li Zhang; Lin Zheng; Hong-yu Jia; Jian-hua Hu; Guo-dong Yu; Jue-qing Gu; Chan-yuan Ye; et al. (Journal of Zhejiang University-SCIENCE B, 2020)

Enhancement of the activity of Cu/TiO2 catalyst by Eu modification for selective catalytic reduction of NOx with NH3 - Yuan-zhen Liu; Qi-yan Xu; Rui-tang Guo; Chao-peng Duan; Gui-lin Wu; Yu-fang Miao; Jing-wen Gu (Environmental Science and Pollution Research, 2020)

Plastic pollution in croplands threatens long‐term food security - Dan Zhang; Ee Ling Ng; Wanli Hu; Hongyuan Wang; Pablo Galaviz; Hude Yang; Wentao Sun; Chongxiao Li; Xingwang Ma; Bin Fu; Peiyi Zhao; Fulin Zhang; et al. (Global Change Biology, 2020)
Plastic pollution is a global concern given its prevalence in aquatic and terrestrial ecosystems. Studies have been conducted on the distribution and impact of plastic pollution in marine ecosystems, but little is known on terrestrial ecosystems. Plastic mulch has been widely used to increase crop yields worldwide, yet the impact of plastic residues in cropland soils to soil health and crop production in the long term remained unclear. In this paper, using a global meta‐analysis, we found that the use of plastic mulch can indeed increase crop yields on average by 25%–42% in the immediate season due to the increase of soil temperature (+8%) and moisture (+17%). However, the unabated accumulation of film residues in the field negatively impacts its physicochemical properties linked to healthy soil and threatens food production in the long term. It has multiple negative impacts on plant growth including crop yield (at the mean rate of −3% for every additional 100 kg/ha of film residue), plant height (−2%) and root weight (−5%), and soil properties including soil water evaporation capacity (−2%), soil water infiltration rate (−8%), soil organic matter (−0.8%) and soil available phosphorus (−5%) based on meta‐regression. Using a nationwide field survey of China, the largest user of plastic mulch worldwide, we found that plastic residue accumulation in cropland soils has reached 550,800 tonnes, with an estimated 6%–10% reduction in cotton yield in some polluted sites based on current level of plastic residue content. Immediate actions should be taken to ensure the recovery of plastic film mulch and limit further increase in film residue loading to maintain the sustainability of these croplands.

Comparison of epidemiological and clinical characteristics of COVID-19 patients with and without Wuhan exposure - Jiang-shan Lian; Huan Cai; Shao-rui Hao; Xi Jin; Xiao-li Zhang; Lin Zheng; Hong-yu Jia; Jian-hua Hu; Shan-yan Zhang; Guo-dong Yu; Jue-qing Gu; Chan-yuan Ye; et al. (Journal of Zhejiang University-SCIENCE B, 2020)

Interaction between serine carboxypeptidase-like protein TtGS5 and Annexin D1 in developing seeds of Triticum timopheevi - Peihong Jiang; JianSheng Gao; Junyi Mu; Luning Duan; Yunsong Gu; Shichen Han; Lin Chen; Yaxuan Li; Yueming Yan; Xiaohui Li (Journal of Applied Genetics, 2020)

Integrated fate assessment of aromatic amines in aerobic sewage treatment plants - Lin Jun Zhou; Zhi Yi Rong; Wen Gu; De Ling Fan; Ji Ning Liu; Li Li Shi; Yan Hua Xu; Zhi Ying Liu (Environmental Monitoring and Assessment, 2020)
The fate and exposure of chemicals in sewage treatment plants (STPs) are major considerations in risk assessment and environmental regulation. The biodegradability and removal of seven aromatic amines were systematically evaluated using a three-tiered integrated method: a standard ready biodegradability test, an aerobic sewage treatment simulation method, and model prediction. In tier 1, the seven aromatic amines were not readily biodegraded after 28 days. In adapted aerobic active sludge, 4-isopropyl aniline, 2,4-diaminotoluene, and 4-nitroaniline among them exhibited the degradation half-life time less than 20 h, the other four aromatic amines exhibited persistent with degradation half-life of > 60 h. In tier 2 of the aerobic sewage treatment simulation testing, 2,4-diaminotoluene, 4-nitroaniline, and 4-isopropylaniline demonstrated moderately to high overall removal. Hydraulic retention time (HRT) affects the removal with the optimum HRT was determined to be 12 h to 24. 2,6-Dimethyl aniline, 2-chloro-4-nitroaniline, 2,6-diethylaniline, and 3,4-dichloroaniline were not removed during the test, indicting these four aromatic amines will enter surface water and hence pose a potential risk to aquatic ecology. Considering the lack of an STP model in China for regulation purposes, in tier 3, we developed a Chinese STP (aerobic) (abbreviated as C-STP(O)) model that reflects a universal scenario for China to predict the fate. The predicted degradation, volatilization, and absorption showed a close relationship to the physicochemical properties of the chemicals, and had same tendency with tier 2 simulation test. The prediction showed that biodegradation rather than absorption or volatilization was the main removal process of aromatic amines in aerobic STP. With the combination of modified kinetics test with C-STP (O) model, the chemical fate can be more accurately predicted than using only the readily biodegradation result.

Analyzing the action of evolutionarily conserved modules on HMW-GS 1Ax1 promoter activity - Luning Duan; Shichen Han; Ke Wang; Peihong Jiang; Yunsong Gu; Lin Chen; Junyi Mu; Xingguo Ye; Yaxuan Li; Yueming Yan; Xiaohui Li (Plant Molecular Biology, 2020)

Evaluation on activation energy of deposited clay based on thermo-gravimetric analysis (TGA) and four kinetics models - Rui-xin Yan; Jian-bing Peng; Yan-jun Shen; Yu-liang Zhang; Lin-jun Gu; Shao-kai Wang (Bulletin of Engineering Geology and the Environment, 2020)

Genome-wide identification of internal reference genes for normalization of gene expression values during endosperm development in wheat - Junyi Mu; Lin Chen; Yunsong Gu; Luning Duan; Shichen Han; Yaxuan Li; Yueming Yan; Xiaohui Li (Journal of Applied Genetics, 2019)

Potential hypoglycemic effect of acetophenones from the root bark of Cynanchum wilfordii - Hao-Wen Jiang; Shan-Shan Gu; Lei Cao; Sheng-Shi Jiang; Jing Lin; Yan Chen; Ling Wang; He Jiao; Jing-Ya Li; Wei-Min Zhao; Jin-Long Li (Natural Product Research, 2019)

Geomagnetic jerk extraction based on the covariance matrix - Yan Feng; Yun-Shan Jiang; Jia-Lin Gu; Fan Xu; Yi Jiang; Shuang Liu (Applied Geophysics, 2019)

Identifying a Major QTL Associated with Salinity Tolerance in Nile Tilapia Using QTL-Seq - Xiao Hui Gu; Dan Li Jiang; Yan Huang; Bi Jun Li; Chao Hao Chen; Hao Ran Lin; Jun Hong Xia (Marine Biotechnology, 2018)

Genome-wide identification and abiotic stress responses of DGK gene family in maize - Yingnan Gu; Changjiang Zhao; Lin He; Bowei Yan; Jiejing Dong; Zuotong Li; Kejun Yang; Jingyu Xu (Journal of Plant Biochemistry and Biotechnology, 2017)

Pharmacological Inhibition of PERK Attenuates Early Brain Injury After Subarachnoid Hemorrhage in Rats Through the Activation of Akt - Feng Yan; Shenglong Cao; Jianru Li; Brandon Dixon; Xiaobo Yu; Jingyin Chen; Chi Gu; Wang Lin; Gao Chen (Molecular Neurobiology, 2017)

Minocycline Protects Against NLRP3 Inflammasome-Induced Inflammation and P53-Associated Apoptosis in Early Brain Injury After Subarachnoid Hemorrhage - Jianru Li; Jingsen Chen; Hangbo Mo; Jingyin Chen; Cong Qian; Feng Yan; Chi Gu; Qiang Hu; Lin Wang; Gao Chen (Molecular Neurobiology, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Epidemiology and characteristics of the dengue outbreak in Guangdong, Southern China, in 2014 - L. Huang; X. Luo; J. Shao; H. Yan; Y. Qiu; P. Ke; W. Zheng; B. Xu; W. Li; D. Sun; D. Cao; C. Chen; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2016)

Radix ranunculus temate saponins induces apoptosis via the death receptor and mitochondrial pathways in SGC-7901 cells - Mao-lin Li; Han-min Gu; Hong-ya Hang; Yao-li Jiang; Jiao Jiang; Qian-na Gu; Wen-yan Wu (Molecular & Cellular Toxicology, 2015)

Human hepatocellular carcinoma-infiltrating CD4+CD69+Foxp3− regulatory T cell suppresses T cell response via membrane-bound TGF-β1 - Yanmei Han; Yuan Yang; Zhubo Chen; Zhengping Jiang; Yan Gu; Yanfang Liu; Sheng Xu; Chuan Lin; Zeya Pan; Weiping Zhou; Xuetao Cao (Journal of Molecular Medicine, 2014)

Comparison of fatty acid and amino acid profiles of steamed Chinese mitten crab - Yan-Ru Guo; Sai-Qi Gu; Xi-Chang Wang; Lin-Min Zhao; Jin-Yuan Zheng (Fisheries Science, 2014)

Organic acids on the growth, anatomical structure, biochemical parameters and heavy metal accumulation of Iris lactea var. chinensis seedling growing in Pb mine tailings - Yu-Lin Han; Su-Zhen Huang; Hai-Yan Yuan; Jiu-Zhou Zhao; Ji-Guang Gu (Ecotoxicology, 2013)

Acid loading stimulates rat glomerular mesangial cells proliferation through Na+–H+ exchanger isoform 1 (NHE1)-dependent pathway - Kun Li; Wei Su; Man Li; Chang-jie Chen; Yong-yu Li; Lin-yun Lai; Ming-min Zhang; Shao-jun Liu; Jakub Fichna; Ai Peng; Chuan-ming Hao; Yong Gu; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2013)

VKORC1-1639G>A, CYP2C9, EPHX1691A>G genotype, body weight, and age are important predictors for warfarin maintenance doses in patients with mechanical heart valve prostheses in southwest China - Qiang Gu; Yan Kong; Jörn Schneede; Ying-Bin Xiao; Lin Chen; Qian-Jin Zhong; Xue-Feng Wang; Jia Hao; Bai-Cheng Chen; Jing-Jin Chen (European Journal of Clinical Pharmacology, 2010)

Cadmium tolerance and accumulation by two species of Iris - Yu-Lin Han; Hai-Yan Yuan; Su-Zhen Huang; Zhi Guo; Bing Xia; Jiguang Gu (Ecotoxicology, 2007)